EFL Students’ Understanding of Moral Values in Reading English Narrative Text - Novita sari; Ahmad Laut Hasibuan; Annisa Zahra Hasibuan; Nazriani Lubis (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2023)
This research deals with students' understanding of moral values ​​in English narrative texts. This research was conducted by students’ of SMP IT Nurul Ikhwan Pantai Cermin. This research focused on